Method for manufacturing composite co-catheter particles coated with a dopamine layer and a pvdf layer

CN122907635APending Publication Date: 2026-10-13SHENZHEN TXD TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610862673.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-06-17
Filing Date
2026-06-15
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0003]传统陶瓷颗粒的表面具有大量的碱性基团(该碱性基团如OH-、Li2O),因此在制程中,当多个传统陶瓷颗粒加入正极浆料后,该多个传统陶瓷颗粒上的该碱性基团会与正极浆料内的溶剂作用,使正极浆料呈强碱性,此会造成正极颗粒与正极浆料的劣化,进而影响制程工艺的难度、且制作出的正极极板的电化学性质容易不如预期

Benefits of technology

[0005]所以本案的目的系为解决上述现有技术上的问题,本案中提出一种制造包覆有多巴胺层及PVDF层的复合助导颗粒的方法,系在原包覆有包覆该多巴胺层的陶瓷颗粒外表面再包覆一层该PVDF层作为保护层,使得该PVDF层进一步保护内部的该二级复合颗粒,而不会与该正极浆料内的溶剂反应导致正极浆料的劣化。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907635A_ABST
    Figure CN122907635A_ABST
Patent Text Reader

Abstract

A method for manufacturing composite conductive particles coated with a dopamine layer and a PVDF layer includes the following steps: step 500: mixing a plurality of composite ceramic particles with a first alcohol solution to form a first mixed slurry; each of the composite ceramic particles is composed of a ceramic particle coated with a dopamine layer on an outer surface; step 510: mixing a PVDF, a second alcohol solution, and an NMP mixed solution to form a second mixed slurry; step 520: mixing the first mixed slurry and the second mixed slurry to form a third mixed slurry; the PVDF forms a PVDF layer coated on the outer surface of the composite ceramic particles; step 530: grinding the third mixed slurry to form a third mixed slurry with higher flowability; and step 540: drying the third mixed slurry with higher flowability to obtain a plurality of composite conductive particle powders.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery cathode material technology, and in particular to a method for manufacturing composite conductive particles coated with a dopamine layer and a PVDF layer. Background Technology

[0002] A battery is mainly formed by placing a positive electrode and a negative electrode in an electrolyte. In existing technology, ceramic particles are added to the negative electrode to increase ionic conductivity. This is because ceramic particles have high ionic conductivity for lithium ions. Therefore, when lithium ions pass through the negative electrode, the dispersed ceramic particles guide them, thus dispersing the lithium ion pathway and allowing for a uniform channel distribution within the positive electrode.

[0003] Traditional ceramic particles have a large number of basic groups on their surface (such as OH groups). - Because of the presence of Li₂O, during the manufacturing process, when multiple traditional ceramic particles are added to the positive electrode slurry, the alkaline groups on these particles react with the solvent in the slurry, making the slurry highly alkaline. This causes degradation of both the positive electrode particles and the slurry, increasing the difficulty of the manufacturing process and making the electrochemical properties of the produced positive electrode plate less than expected. Current technology includes coating the traditional ceramic particles with a dopamine layer to protect them; however, this dopamine layer cannot completely cover the outer surface of the ceramic particles, leaving a small portion of the particle surface exposed.

[0004] Therefore, this case aims to propose a novel method for manufacturing composite conductive particles coated with a dopamine layer and a PVDF layer, in order to overcome the aforementioned deficiencies in the prior art. Summary of the Invention

[0005] Therefore, the purpose of this case is to solve the aforementioned problems in the prior art. This case proposes a method for manufacturing composite conductive particles coated with a dopamine layer and a PVDF layer. The method involves coating the outer surface of the ceramic particles originally coated with the dopamine layer with another PVDF layer as a protective layer. This allows the PVDF layer to further protect the internal secondary composite particles and prevent them from reacting with the solvent in the positive electrode slurry, thus preventing the deterioration of the positive electrode slurry.

[0006] To achieve the above objectives, this invention proposes a method for manufacturing composite conductive particles coated with a dopamine layer and a PVDF layer, wherein the composite conductive particles are disposed within a slurry layer of an electrode; the method includes the following steps: Step 500: taking multiple composite ceramic particles and a first alcohol solution and placing them into a first mixer to mix and form a first mixed slurry; each composite ceramic particle is composed of ceramic particles coated with a dopamine layer; the dopamine layer is composed of polydopamine molecules; wherein the dopamine layer cannot completely cover the outer surface of the ceramic particles, so a small portion of the surface of the ceramic particles will still be exposed; the ceramic particles have high ionic conductivity for lithium ions; the ceramic... Ceramic particles are used to guide and disperse lithium ions, preventing abnormal accumulation of lithium ions in the electrode slurry and causing side reactions with the electrode slurry. Step 510: A mixed solution of PVDF, a second alcohol solution, and NMP is placed in a second mixer to form a second mixed slurry. Step 520: The first and second mixed slurries are placed in an emulsifier to form a third mixed slurry. At this time, the multiple composite ceramic particles in the first mixed slurry will react with the PVDF in the second mixed slurry. Some of the fluoride ions in the PVDF will form ionic bonds with the lithium ions on the surface of the corresponding ceramic particles to form lithium fluoride. The other part of the PVDF... The fluoride ions will form hydrogen bonds with the nitrogen ions of the dopamine layer on the surface of the composite ceramic particles, thus forming a PVDF layer that coats the outer surface of the composite ceramic particles. The PVDF layer and the corresponding composite ceramic particles form the composite conductive particles. In this step, the PVDF and the composite ceramic particles will form multiple agglomerates due to their chemical properties, causing the third mixed slurry to gel and become a giant structure. Step 530: The gelled third mixed slurry is placed in a grinding mill for grinding to form a more fluid third mixed slurry, that is, the multiple composite ceramic particles and the multiple agglomerates formed by the PVDF in the gelled third mixed slurry are ground. The PVDF particles are ground into stable and fine particles. After physical and mechanical grinding by the grinding machine, the giant structure can be destroyed, and the originally agglomerated PVDF can be transformed back into fine PVDF fragments, which still have the original properties of PVDF. The PVDF fragments fill the exposed areas of the ceramic particles. Therefore, this grinding step makes the composite conductive particles more stable and finer. Thus, a third mixed slurry with high flowability is formed. Step 540: The third mixed slurry with high flowability is placed in a vacuum thickener for drying to remove the first alcohol solution, the second alcohol solution and the NMP in the third mixed slurry, thereby obtaining a plurality of powders composed of the composite conductive particles.

[0007] The features and advantages of this work will be further explained in the following description; please refer to the accompanying drawings while reading. Attached Figure Description

[0008] Figure 1 This diagram shows the steps involved in this case.

[0009] Figure 2 This document displays the operation flowchart for this case.

[0010] Figure 3 This shows a cross-sectional view of the structure of this case.

[0011] Figure 4 This example demonstrates the application of this case.

[0012] The components include: electrode 10, electrode substrate 11, electrode slurry 12, electrode slurry layer 13, ceramic particles 15, dopamine layer 35, PVDF 40, PVDF layer 41, composite conductive particles 100, composite ceramic particles 110, first alcohol solution 111, mixed solution 112, first mixed slurry 120, second mixed slurry 130, third mixed slurry 140, first mixer 600, second mixer 610, emulsifier 620, mill 630, and vacuum concentrator 640. Detailed Implementation

[0013] Please refer to Figures 1 to 4 The diagram illustrates a method for manufacturing composite conductive particles coated with a dopamine layer and a PVDF layer, wherein the composite conductive particles 100 are primarily used in the electrode 10 of a solid-state or near-solid-state battery. In application, multiple composite conductive particles 100 can be disposed within the electrode 10, which is particularly the positive electrode of the solid-state or near-solid-state battery. The particle size of the composite conductive particles 100 is less than 300 nanometers. The electrode 10 includes an electrode substrate 11, a carrier material for supporting the electrode 10; an electrode slurry layer 13 is coated on the electrode substrate 11, the electrode slurry layer 13 includes an electrode slurry 12 as a binder, and the electrode slurry layer 13 further includes multiple composite conductive particles 100. The weight percentage of the multiple composite conductive particles 100 in the electrode slurry layer 13 is between 2 wt% and 10 wt%.

[0014] The method for manufacturing the composite conductive particles 100 in this case is as follows: Figure 1 As shown, it includes the following steps: Step 500: Take multiple composite ceramic particles 110 and a first alcohol solution 111 and place them into a first mixer 600 for mixing to form a first mixed slurry 120. Each composite ceramic particle 110 is composed of ceramic particles 15 coated with a dopamine layer 35. The dopamine layer 35 is composed of polydopamine molecules. The bonding method between the polydopamine molecules and the ceramic particles 15 is well known in the prior art and will not be described in detail here. For example, the ceramic particles 15 are bonded to OH groups via external hydrogen bonds.- bonds with the OH groups in dopamine - for dehydration polymerization. The ceramic particles 15 have a particle size of less than 100 nanometers; wherein the dopamine layer 35 has a thickness ranging from 2 nanometers to 15 nanometers. The dopamine layer 35 cannot completely cover the outer surface of the ceramic particles 15, so a small portion of the surface of the ceramic particles 15 remains exposed.

[0015] wherein the first alcohol solution 111 is selected from methanol, ethanol, isopropanol and the like. The proportion of the total weight of the composite ceramic particles 110 in the first mixed slurry 120 (i.e., solid content ratio) ranges from 5 wt% to 10 wt%, preferably 9 wt%.

[0016] The ceramic particles 15 have high ionic conductivity for lithium ions. Therefore, when lithium ions pass through the electrode 10, the ceramic particles 15 are used to guide and disperse the lithium ions, so that uniformly distributed lithium ion channels can be formed in the electrode 10, preventing abnormal accumulation of lithium ions in the electrode slurry 12 that would cause side reactions with the electrode slurry 12. The ceramic particles 15 are oxides with a garnet or perovskite structure. Examples of the oxides with a garnet or perovskite structure include lithium lanthanum zirconium oxide (Li7La3Zr2O 12 , lithium lanthanum zirconium oxide, LLZO) or at least one of lithium lanthanum titanium oxide (lithium lanthanum titanium oxide, LLTO).

[0017] wherein when the ceramic particles 15 are made of LLZO, the LLZO material is formed from at least one selected from LLZO, Ga-LLZO (Ga-doped LLZO), Cu-LLZO (Cu-doped LLZO), Ta-LLZO (Ta-doped LLZO), Sr-LLZO (Sr-doped LLZO), and Al-LLZO (Al-doped LLZO).

[0018] When the ceramic particles 15 are made of LLTO, the lithium lanthanum titanium oxide is Li 3x La 2 / (3-x) TiO3, where 0<x<0.167, such as Li 0.33 La 0.56 TiO3, at least one of Ga-doped lithium lanthanum titanium oxide, Cu-doped lithium lanthanum titanium oxide, Ta-doped lithium lanthanum titanium oxide, Sr-doped lithium lanthanum titanium oxide, and Al-doped lithium lanthanum titanium oxide.

[0019] Step 510: Take 40g of PVDF (polyvinylidene difluoride), 40g of the second alcohol solution, and 112g of NMP (N-methylpyrrolidone) and place them into a second mixer 610 to mix and form a second mixed slurry 130. The second alcohol solution is selected from methanol, ethanol, and isopropanol, etc. The first alcohol solution 111 and the second alcohol solution can be selected from the same alcohol solution. In the mixed solution 112, the weight ratio of the second alcohol solution to the NMP is 0.85:0.15.

[0020] The PVDF 40 accounts for a weight percentage (i.e., solid content) of the second mixed slurry 130 between 0.5 wt% and 0.8 wt%. The total weight of the PVDF 40 is in a weight ratio of 1:50 to the total weight of the composite ceramic particles 110.

[0021] Step 520: The first mixed slurry 120 and the second mixed slurry 130 are placed in an emulsifier 620 for mixing to form a third mixed slurry 140. At this time, the plurality of composite ceramic particles 110 in the first mixed slurry 120 will react with the PVDF 40 in the second mixed slurry 130, and some of the fluoride ions (F ions) in the PVDF 40 will react. - ) will react with lithium ions (Li) on the surface of the corresponding ceramic particles 15 + The ionic bonds formed in this PVDF 40 create lithium fluoride (LiF); while the other portion of the fluoride ions (F) in this PVDF 40... - ) will react with the nitrogen ions (N) of the dopamine layer 35 on the surface of the composite ceramic particles 110. - Hydrogen bonds are formed, thus the PVDF 40 forms a PVDF layer 41 covering the outer surface of the composite ceramic particle 110. The PVDF layer 41 and the corresponding composite ceramic particle 110 form the composite conductive particle 100 (e.g., Figure 3 (As shown). In this step, the PVDF 40 and the composite ceramic particles 110 will form multiple agglomerates due to their chemical properties, causing the third mixed slurry 140 to curing into a giant structure.

[0022] In step 520, the mixing time is 30 minutes to 1 hour. The thickness of the PVDF layer 41 is between 10 nanometers and 100 nanometers.

[0023] The purpose of coating the PVDF layer 41 is that solvents are present during the manufacturing process of the electrode paste 12. Since the ceramic particles 15 are hydrophilic, although the dopamine layer 35 coats the outer surface of the ceramic particles 15, it cannot completely cover the outer surface. Therefore, a small portion of the surface of the ceramic particles 15 remains exposed. This exposed surface has a large number of basic groups (such as OH groups). - When multiple composite ceramic particles 110 are added to the positive electrode slurry (e.g., Li₂O), the alkaline groups of the composite ceramic particles 110 react with the solvent in the positive electrode slurry, making the positive electrode slurry strongly alkaline. This causes degradation of both the positive electrode particles and the positive electrode slurry, which in turn affects the difficulty of the manufacturing process and makes the electrochemical properties of the produced positive electrode plate less than expected. Therefore, by coating the dopamine layer 35 with a PVDF layer 41, the reaction between the ceramic particles 15 and the solvent in the electrode slurry 12 can be completely isolated, improving battery performance.

[0024] Step 530: The gelled third mixed slurry 140 is placed in a grinder 630 for grinding to form a more fluid third mixed slurry 140. That is, the multiple aggregates formed by the multiple composite ceramic particles 110 and the PVDF 40 in the gelled third mixed slurry 140 are ground into stable and fine particles. After physical and mechanical grinding by the grinder 630, the giant structure can be broken down, so that the originally agglomerated PVDF 40 becomes fine PVDF fragments, which still have the original properties of PVDF. These PVDF fragments can fill the exposed areas of the ceramic particles 15. Therefore, this grinding step can make the composite conductive particles 100 more stable and finer, and also promote the completion of the reaction. The particle size of the composite conductive particles 100 is less than 300 nanometers.

[0025] Therefore, the third mixed slurry 140 with high flowability is formed. The grinding time in step 530 is 1.5 hours to 2 hours.

[0026] Step 540: The highly fluid third mixed slurry 140 is placed in a vacuum thickener 640 for drying to remove the first alcohol solution 111, the second alcohol solution and the NMP from the third mixed slurry 140, thereby obtaining a plurality of powders composed of the composite guiding particles 100.

[0027] The advantage of this invention is that a PVDF layer is then coated on the outer surface of the ceramic particles originally coated with the dopamine layer as a protective layer. This PVDF layer further protects the internal secondary composite particles and prevents them from reacting with the solvent in the positive electrode slurry, thus preventing the positive electrode slurry from deteriorating.

[0028] The above detailed description is a specific description of a feasible embodiment of this case. However, this embodiment is not intended to limit the scope of the patent in this case. All equivalent implementations or modifications that do not depart from the spirit of the technology in this case should be included in the scope of the patent in this case.

Claims

1. A method for manufacturing composite conductive particles coated with a dopamine layer and a PVDF layer, characterized in that, The composite conductive particles are disposed within the slurry layer of an electrode; the method includes the following steps: Step 500: Take multiple composite ceramic particles and place them into a first alcohol solution in a first mixer to mix and form a first mixed slurry; each composite ceramic particle is composed of ceramic particles coated with a dopamine layer on the outer surface; the dopamine layer is composed of polydopamine molecules; wherein the dopamine layer cannot completely cover the outer surface of the ceramic particles, so a small portion of the surface of the ceramic particles will still be exposed; The ceramic particles have high ionic conductivity for lithium ions; they are used to guide and disperse lithium ions, preventing abnormal accumulation of lithium ions in the electrode slurry and avoiding side reactions with the electrode slurry. Step 510: Take a mixed solution of PVDF, the second alcohol solution and NMP and put it into a second mixer to mix and form a second mixed slurry; Step 520: The first and second mixed slurries are placed in an emulsifier for mixing to form a third mixed slurry. At this time, the multiple composite ceramic particles in the first mixed slurry react with the PVDF in the second mixed slurry. Some of the fluoride ions in the PVDF form ionic bonds with the lithium ions on the surface of the corresponding ceramic particles to form lithium fluoride. Other fluoride ions in the PVDF form hydrogen bonds with the nitrogen ions in the dopamine layer on the surface of the composite ceramic particles. Therefore, the PVDF forms a PVDF layer that coats the outer surface of the composite ceramic particles. The PVDF layer and the corresponding composite ceramic particles form the composite conductive particles. In this step, the PVDF and the composite ceramic particles form multiple aggregates due to their chemical properties, causing the third mixed slurry to gel and become a giant structure. Step 530: The gelled third mixed slurry is placed in a grinding mill for grinding to form a highly flowable third mixed slurry. That is, the multiple composite ceramic particles and multiple agglomerates formed by the PVDF in the gelled third mixed slurry are ground into stable and fine particles. After physical and mechanical grinding by the grinding mill, the giant structure can be destroyed, so that the originally agglomerated PVDF becomes fine PVDF fragments, which still have the original properties of PVDF. The PVDF fragments fill the exposed places of the ceramic particles. Therefore, this grinding step makes the composite conductive particles more stable and finer; thus forming a highly flowable third mixed slurry. Step 540: The highly fluid third mixed slurry is placed in a vacuum thickener for drying to remove the first alcohol solution, the second alcohol solution and the NMP from the third mixed slurry, thereby obtaining a plurality of powders composed of the composite guiding particles. The ceramic particles are oxides with garnet or perovskite structures.

2. The method for manufacturing composite conductive particles coated with a dopamine layer and a PVDF layer as described in claim 1, characterized in that, In step 500, the size of the ceramic particles is less than 100 nanometers; and the thickness of the dopamine layer is between 2 nanometers and 15 nanometers.

3. The method for manufacturing composite conductive particles coated with a dopamine layer and a PVDF layer as described in claim 1, characterized in that, The first alcohol solution is selected from at least one of methanol, ethanol and isopropanol; the second alcohol solution is selected from at least one of methanol, ethanol and isopropanol.

4. The method for manufacturing composite conductive particles coated with a dopamine layer and a PVDF layer as described in claim 1, characterized in that, The total weight of the composite ceramic particles accounts for between 5 wt% and 10 wt% of the first mixed slurry.

5. The method for manufacturing composite conductive particles coated with a dopamine layer and a PVDF layer as described in claim 5, characterized in that, The oxide with a garnet or perovskite structure is lithium lanthanum zirconium oxide.

6. The method for manufacturing composite conductive particles coated with a dopamine layer and a PVDF layer as described in claim 5, characterized in that, When the ceramic particles are composed of lithium lanthanum zirconium oxide, the lithium lanthanum zirconium oxide is Li7La3Zr2O. 12 At least one of the following: gallium-doped lithium lanthanum zirconium oxide, copper-doped lithium lanthanum zirconium oxide, tantalum-doped lithium lanthanum zirconium oxide, strontium-doped lithium lanthanum zirconium oxide, and aluminum-doped lithium lanthanum zirconium oxide.

7. The method for manufacturing composite conductive particles coated with a dopamine layer and a PVDF layer as described in claim 1, characterized in that, The oxide with a garnet or perovskite structure is selected from lithium lanthanum titanium oxide.

8. The method for manufacturing composite conductive particles coated with a dopamine layer and a PVDF layer as described in claim 7, characterized in that, The lithium lanthanum titanium oxide is Li 3x La 2 / (3-x) TiO3, where 0<x<0.167, which is at least one selected from gallium-doped lithium lanthanum titanium oxide, copper-doped lithium lanthanum titanium oxide, tantalum-doped lithium lanthanum titanium oxide, strontium-doped lithium lanthanum titanium oxide, and aluminum-doped lithium lanthanum titanium oxide.

9. The method for manufacturing composite conductive particles coated with a dopamine layer and a PVDF layer as described in claim 1, characterized in that, In the mixed solution, the weight ratio of the second alcohol solution to the NMP is 0.85:0.15; the weight percentage of PVDF in the second mixed slurry is between 0.5 wt% and 0.8 wt%; and the weight ratio of the total weight of PVDF to the total weight of the composite ceramic particles is 1:

50.

10. The method for manufacturing composite conductive particles coated with a dopamine layer and a PVDF layer as described in claim 1, characterized in that, In step 520, the mixing time is 30 minutes to 1 hour.

11. The method for manufacturing composite conductive particles coated with a dopamine layer and a PVDF layer as described in claim 1, characterized in that, In step 520, the thickness of the PVDF layer is between 10 nanometers and 100 nanometers.

12. The method for manufacturing composite conductive particles coated with a dopamine layer and a PVDF layer as described in claim 1, characterized in that, In step 530, the particle size of the composite guiding particle is less than 300 nanometers.

13. The method for manufacturing composite conductive particles coated with a dopamine layer and a PVDF layer as described in claim 1, characterized in that, The grinding time in step 530 is 1.5 hours to 2 hours.